Kurikulum Masjid dan Radikalisme: Strategi Ta'mir Masjid Cegah Konten Radikal di Kota Palembang - Abdurrahmansyah, Abdurrahmansyah; Saputra, Ade Akhmad; Chandra, Vicky; Fatrin, Juan Muliawan; Nasution, Nurseri Hasnah (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This research analyzes the strategies used by mosque administrators in developing a mosque studies curriculum to combat the spread of radical Islamic ideology. The method used is qualitative with a case study approach. Primary data sources are the chairman of the mosque takmir and the head of the Idarah and Imarah section who is responsible for making decisions on mosque management, including the recitation schedule. Secondary sources include mosque congregations involved in mosque activities. Data collection methods include interviews, documentation, and observation. The data analysis process includes data collection, reduction, presentation and drawing conclusions. The study concluded that the main strategy is strict selection of Friday preachers and preachers to prevent the spread of radical views. Mosque administrators also regularly assess the competence of the preacher and reject parties who could cause divisions among the congregation. The current study curriculum is simple, consisting of a preaching schedule and study at books such as Riyadush Shalihin and Adabul Mufrad. However, there is no systematic and comprehensive curriculum structure. Mosque management coordinates with the Ministry of Religion to ensure the quality of preaching and quality of mosque.